The Analysis Study of Prevalence, Diagnosis and Management of Allergic Conjunctivitis: A Comprehensive Systematic Review - Iffan Soffyan Ismail; Yuce Yuanita (International Medical Journal Corp. Ltd, 2024)
Background: Allergic conjunctivitis (AC) is a common ocular condition that significantly impacts the quality of life of individuals worldwide. This systematic review aims to provide a comprehensive overview of the prevalence, diagnostic approaches, and management strategies for allergic conjunctivitis. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Allergic conjunctivitis is common and impacts quality of life. Management includes pharmacologic and non-pharmacologic treatments, with dual-acting antihistamine-mast cell stabilizers being key. Many remain undiagnosed or inadequately treated, highlighting the need for improved awareness, diagnostics, and future research.